Relationship Between the Duration of Haemodialysis and the Nutritional Status of Chronic Kidney Failure Patients in Kupang City - Easter Tiur Lumban Gaol; Teguh Dwi Nugroho; Efrisca M. Damanik; Christina Olly Lada (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Hemodialysis is a treatment that begins once a person is identified as having end-stage chronic kidney disease (CKD) and will continue for the duration of their life or until the individual has a kidney transplant. Nevertheless, many CKD patients receiving hemodialysis often face issues with malnutrition. This research aimed to explore how the length of time spent on hemodialysis affects the nutritional health of CKD patients in Kupang City. The study used an observational analytical method with a cross-sectional approach through direct interviews and Body Mass Index (BMI) measurements. Sampling was conducted using consecutive sampling with 110 patients, and analysis was performed using the Chi-Square test. The findings revealed that a large portion of participants fell within the age range of 41 to 60 years (47.3%) and that most were male (57.3%). Hypertension emerged as the most prevalent comorbidity, affecting 32.9% of the subjects. A significant number of individuals received hemodialysis two times a week (84.5%) and had been undergoing this treatment for over 24 months (37.3%). The bivariate analysis indicated no notable connection between the length of hemodialysis and nutritional health as defined by BMI (P>0.05), yet a significant association was found between the duration of hemodialysis and nutritional health assessed via the Simple Nutrition Screening Tool (P<0.05). Consistent nutritional assessments using the Simple Nutrition Screening Tool are essential for all hemodialysis patients to identify malnutrition risks early, allowing timely and appropriate dietary interventions. It is recommended that patients focus more on their nutritional habits and follow dietary guidelines set by nutritionists to avoid malnutrition and its associated issues.